2005
DOI: 10.1089/pho.2005.23.202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Aminolevulic Acid Photodynamic Therapy plus Pulsed Dye Laser versus Pulsed Dye Laser Alone in Treatment of Viral Warts

Abstract: All three therapeutic methods are able to cure infectious warts with high probability (>80%). However, a combination of PDT and PDL is the most effective and the most favored therapy. If other investigators also confirm results near or equal to 100% success, this therapy could become a treatment of choice for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 10 publications
(10 reference statements)
0
37
0
3
Order By: Relevance
“…Ninety-six percent (73/76) of warts were cured in 2.54 sessions using photodynamic therapy with aminolevulinic acid-induced protoporphyrin as a photosensitizer, 293 and 100% (86/86) of warts were cured when the therapeutic modalities were combined. 294 Warts in a variety of locations were treated. These cure rates are very promising, but no information on recurrence was provided.…”
Section: Photoselective Dye Laser + Photosensitizer For Photodynamic mentioning
confidence: 99%
“…Ninety-six percent (73/76) of warts were cured in 2.54 sessions using photodynamic therapy with aminolevulinic acid-induced protoporphyrin as a photosensitizer, 293 and 100% (86/86) of warts were cured when the therapeutic modalities were combined. 294 Warts in a variety of locations were treated. These cure rates are very promising, but no information on recurrence was provided.…”
Section: Photoselective Dye Laser + Photosensitizer For Photodynamic mentioning
confidence: 99%
“…Until recently, the main application of PDT was to treat malignant and some benign lesions; 1,2 however, the efficacy of this procedure for microbial reduction has been demonstrated in several studies. [3][4][5][6] This emerging class of applications, which we refer to as antimicrobial photodynamic action (APDA), shows great potential. [7][8][9][10] Currently, lasers are the most common light sources used to activate the photosensitizers.…”
mentioning
confidence: 99%
“…A study on the viral wart showed that PDT using an LED source achieved clearance rates of 81% (mean of 3.34 treatments). 4 Complete clearance of periungula hand warts in 18 of 20 patients (30 of 40 warts) was achieved in a pilot study of PDT with ALA after a mean of 4.5 treatments. 7 PDT leads to the release of inflammatory mediators, like interleukin 2, interleukin 1-b, and tumour necrosis factora, 9 suggesting that another mechanism for the clearance of these cells is in the indirect stimulation of local immune responses in the lesion area.…”
Section: Discussionmentioning
confidence: 99%
“…Topical photodynamic therapy (PDT) offers an effective and non-invasive treatment with good cosmetic outcome for intraepithelial neoplasia and inflammatory dermatosis, such as psoriasis and viral warts. [2][3][4] PDT with 10-20% Methyl aminolaevulinate (MAL) has been reported in successfully treating periungual warts and superficial squamous cell carcinoma (SCC), and has been approved in treating actinic keratosis (AK) and Bowen's disease (BD) that are intraepithelial SCC. [5][6][7] These disorders and PEH share similar histological features, namely epidermal hyperplasia.…”
mentioning
confidence: 99%